Coccidiose em frangos de corte: revisão bibliográfica - Araujo, Matheus Aparecido Niedo (2021)
Maintaining the health of animals in captivity is essential to obtain good levels of productivity and profitability. At aviaries the health is extremely important considering that adult chicks and chickens can be affected with diseases and problems with the environment when it is not well managed. Diseases such as avian coccidiosis cause countless losses to the agricultural sector, which makes the producer face numerous problems if he does not perform good care in the care of the chickens. The aim of this study was to carry out a bibliographic survey, in order to better understand the aspects related to coccidiosis, such as the characteristics of protozoa, the pathogenesis and possible methods of prevention, control and how the diagnosis is made in broiler chickens. It was possible to verify that the species E. acervulina, E. maxima, and E. tenella are the most economically important due to their geographical dissemination capacity and the severity of symptoms when infection occurs in broiler poultry houses. Control can be carried out with measures that can help prevent outbreaks of this disease, such as cleaning the sheds, strictly following a sanitary control program, following an appropriate medication protocol, in addition to adopting the proper management of the aviary. After a brief analysis of works related to coccidiosis in broilers, it is necessary to understand that this disease is very demanding in terms of attention and care, as it causes a high economic loss for poultry producers. Despite technification and advances in science regarding research, treatments and medicines to improve the life of chickens, the management of coccidiosis requires a serious commitment to ensure a reduction in its incidence, it is enough to comply with sanitary requirements in a good anticoccidial planning.